Defining and Responding to Bullying - Huk, Oksana (International Journal For Research In Educational Studies, 2019)
Concerns have been raised over the definition used for bullying across research and practice settings due to its subjective nature, and because it is not used consistently. As bullying can lead to very serious consequences for those affected by it, it is necessary to prevent, identify, and respond to it with competence. One possible avenue to increase research in is the use of cognitive behavioral therapy as means to address bullying in schools, as by its nature CBT is tailored to subjective interpretations of events. Rational Emotive Behavior Therapy is one subset of CBT, where new research shows some promising results in at least the cognitive and emotional consequences resulting from bullying.